Simultaneous Detection and Quantification of Four Sulfonamides in Buffalo Meat using RP-HPLC - Kalpana, S.; Rao, Ch.Umamaheswara; Muthukumar , M. (Journal of Meat Science, 2022)
A multi-residue analysis of four sulfonamides viz., sulfadiazine,  sulfadoxine, sulfamethazine, sulfamethoxazole in buffalo meat has been  proposed using HPLC- UV detection method. Samples were extracted  by liquid-liquid extraction using acetonitrile, n-hexane solution and  the analysis was carried out using a reverse phase HPLC using UV  detector. The chromatographic separation was achieved using mobile  phase consisting of glacial acetic acid in acetonitrile, methanol and water  (85:10:5, v/v) in an isocratic elution mode. The volume of injection and  flow rate of the mobile phase were 40 µl and 1.5 ml/min respectively.  UV detector was operated at a wavelength 254 nm. Specificity, linearity,  recovery percentage, intra-day variation, limit of detection (LOD),  limit of quantification (LOQ) were evaluated in buffalo meat matrix at  drug concentrations ranging from 10-500µg/Kg. Extraction recoveries  of sulfonamides viz., sulfadiazine, sulfadoxine, sulfamethazine,  sulfamethoxazole were ranged to be 72-77, 79-83, 85-89 and 82-86%  respectively. The LOD for Sulfonamides viz., sulfadiazine, sulfadoxine,  sulfamethazine, sulfamethoxazole were 6.06, 7.63, 6.79 and 10.68 µg/Kg  and the LOQ were 18.37, 23.12, 20.57 and 32.37 µg/Kg, respectively. The  proposed RP-HPLC method is quite adequate for routine monitoring of  residual sulfonamides in buffalo meat below Codex MRL (100 µg/Kg).
Keywords: RP-HPLC; Buffalo meat; Tissue residues; Sulfonamides; liquid-liquid extraction